Annotated record of the detailed examination of Mn deposits from the 7TOW cruise among the Line Islands Guyots in the Pacific Ocean - James H Natland (PANGAEA, 1976)
Volcanic rocks dredged from the tops of seamounts in the Line Islands and cored from their flanks demonstrate that this is a region of extreme petrologic diversity. Tholeiitic and alkalic basalts were obtained in a single dredge haul and a wide spectrum of alkalic differentiates, including quartz trachytes, and phonolites were dredged or cored elsewhere. Four dredge stations on widely scattered seamounts recovered potassic nephelinites, unlike any other volcanic rocks heretofore found in the ocean basins. These rocks include amphibole and biotite-bearing varieties, some of which are leucite normative.
Supplement to: Natland, JH (1976): Petrology of Volcanic Rocks Dredged from Seamounts in the Line Islands. In: Schlanger, S.O.; Jackson, E.D.; et al., Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, XXXIII, 749-777, https://doi.org/10.2973/dsdp.proc.33.126.1976